A counterintuitive perspective for the role of fat‐free mass in metabolic health. Issue 2 (30th January 2020) - Lagacé, Jean‐Christophe; Brochu, Martin; Dionne, Isabelle J.
Abstract: Fat‐free mass (FFM) has long been recognized to play a role in metabolic homeostasis. Over the years, it has become widely accepted by the scientific and general community alike that having a greater FFM can be protective for metabolic health. Hence, in the context of an aging population concurrently facing sarcopenia and an elevated incidence of metabolic diseases, substantial efforts are being made to study and develop interventions aiming to maintain or increase FFM. However, accumulating evidence now suggests that a large FFM may be deleterious to metabolic health, at least in some populations. The objective of this article is thus to raise awareness surrounding these results and to explore possible explanations and mechanisms underlying this counterintuitive association.